2003
DOI: 10.1016/j.cub.2003.09.056
|View full text |Cite
|
Sign up to set email alerts
|

The Sac1 Lipid Phosphatase Regulates Cell Shape Change and the JNK Cascade during Dorsal Closure in Drosophila

Abstract: The Sac1 lipid phosphatase dephosphorylates several phosphatidylinositol (PtdIns) phosphates and, in yeast, regulates a diverse range of cellular processes including organization of the actin cytoskeleton and secretion. We have identified mutations in the gene encoding Drosophila Sac1. sac1 mutants die as embryos with defects in dorsal closure (DC). DC involves the migration of the epidermis to close a hole in the dorsal surface of the embryo occupied by the amnioserosa. It requires cell shape change in both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…Subsequently, Sac1p, an essential gene in yeast, has been shown to regulate PI(4)P levels and to play important roles in the Golgi apparatus, actin cytoskeleton dynamics, and other cellular functions (Hughes et al, 2000;Foti et al, 2001). Studies in Drosophila melanogaster have shown that mutation of Sac1 results in disruption of JNK mitogen-activated protein kinase signaling, resulting in embryo lethality (Wei et al, 2003). It is intriguing that, in plants, the rhd4-1 null allele has defective root hairs but no other observed morphological defects.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Sac1p, an essential gene in yeast, has been shown to regulate PI(4)P levels and to play important roles in the Golgi apparatus, actin cytoskeleton dynamics, and other cellular functions (Hughes et al, 2000;Foti et al, 2001). Studies in Drosophila melanogaster have shown that mutation of Sac1 results in disruption of JNK mitogen-activated protein kinase signaling, resulting in embryo lethality (Wei et al, 2003). It is intriguing that, in plants, the rhd4-1 null allele has defective root hairs but no other observed morphological defects.…”
Section: Discussionmentioning
confidence: 99%
“…All of these defects can be rescued by overexpression of Sac1, and both its catalytic activity and ability to cycle between the ER and the Golgi were required for complementation (929). Sac1 mutant flies also die in embryonic stage and develop dorsal closure defects (1689). The structure of yeast Sac1 has been recently solved at 2 Ă… resolution.…”
Section: R(t/s) Motif Within Their Catalytic Domains (Figure 8bmentioning
confidence: 99%
“…For example, mutations affecting the Drosophila PtdIns(4)P 5-kinase Skittles (Sktl) are lethal and clones of sktl mutant cells are largely inviable, making it difficult to assess PtdIns(4,5)P 2 function in vivo (Hassan et al, 1998). Similarly, the PtdIns 4-phosphatase Sac1 is essential, limiting analysis of the consequences of PtdIns(4)P overproduction (Wei et al, 2003). In the course of studies examining PtdIns(4,5)P 2 function in Drosophila male-germ-cell cytokinesis, we depleted plasma membrane PtdIns(4,5)P 2 by targeted expression of a lipid phosphatase (Wong et al, 2005).…”
Section: Introductionmentioning
confidence: 99%